2005
DOI: 10.1177/1532673x04270521
|View full text |Cite
|
Sign up to set email alerts
|

Group-Based Resources and Political Participation among Asian Americans

Abstract: Scholars of minority political participation have shown significant interest in unraveling the complex but crucial role of group-based resources. Although there is an emerging scholarship on Latinos, much of the work on group consciousness, group identity, and ethnic organizations is based on research on Black Americans. Increasing diversity in the United States brings necessary attention to expanding the model to the politics and participation of other non-White, multiethnic, and immigrant majority communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 28 publications
3
123
0
Order By: Relevance
“…The discussion in this paper is closely related to studies that emphasize the role of racial and ethnic consciousness on political participation: the strong consciousness of a ''common fate'' with other members of the group and/or dissatisfaction with the current political and material resources available to the group often lead one to be more likely to participate (e.g., Leighley and Vedlitz 1999;Lien 1994;Stokes 2003;Wong et al 2005;Wrinkle et al 1996). Although these studies also implicitly posit a similar argument of participation motivated by perceptions of group-level participatory benefits, our discussion can be distinguished from theirs in that these perceptions are not simply treated as another individual trait but rather modeled as a function of various aspects of racial contexts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The discussion in this paper is closely related to studies that emphasize the role of racial and ethnic consciousness on political participation: the strong consciousness of a ''common fate'' with other members of the group and/or dissatisfaction with the current political and material resources available to the group often lead one to be more likely to participate (e.g., Leighley and Vedlitz 1999;Lien 1994;Stokes 2003;Wong et al 2005;Wrinkle et al 1996). Although these studies also implicitly posit a similar argument of participation motivated by perceptions of group-level participatory benefits, our discussion can be distinguished from theirs in that these perceptions are not simply treated as another individual trait but rather modeled as a function of various aspects of racial contexts.…”
Section: Resultsmentioning
confidence: 97%
“…While a part of the differential in participation rates across different racial groups can be explained by uneven distribution in resources (Verba et al 1993;Wolfinger and Rosenstone 1980) or varying exposure to mobilization efforts (Rosenstone and Hansen 1993), Latinos and Asian Americans are distinguished from the rest of the electorate in terms of their political opportunities and incentives (e.g., DeSipio 1996). For instance, scholars have found that another set of variables due to their particular status as immigrant-majority and racialminority groups significantly affects their active participation in politics: for instance, length of residence and nativity (Bass and Casper 2001;Lien 2004;Ramakrishnan 2005), English proficiency (Cho 1999), the extent of acculturation (Lien 1994), experiences of discrimination (Schildkraut 2005), group consciousness (Leighley and Vedlitz 1999;Stokes 2003;Uhlaner et al 1989;Wong et al 2005), and religious or non-religious organizational membership (Diaz 1996;Jones-Correa and Leal 2001).…”
mentioning
confidence: 98%
“…Wong, Lien and Conway (2005) find that immigrants (especially foreign-born non US citizens) are less likely to donate money to political parties than US born citizens. Frey and Meier (2004a; find that immigrant students are less likely to donate to social funds of their university than native students.…”
Section: Immigration and Citizenship Statusmentioning
confidence: 86%
“…Moreover, it has an indirect effect in promoting forms of political involvement among immigrants for which citizenship is not a legal requirement (Leal 2002, Vargas-Ramos 2003, Fraga et al 2010, cf. DeSipio 1996, Wong et al 2005.…”
mentioning
confidence: 99%